KOTRIBUSI PAJAK PENRANGAN JALAN TERHADAP PAJAK DAERAH KABUPATEN TABALONG TAHUN 2015 S.D 2018 - Elmi Yusuf; Ayu Oktaviani (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2020)
Local taxes are taxes that are run by local governments with the aim of developing in their respective regions. This final project is to find out the contribution of street lighting taxation to local taxes